Cooperative CO2 absorption by amino acid-based ionic liquids with balanced dual sites. Issue 13 (25th February 2020) - Chen, Xiaoyan; Luo, Xiaoyan; Li, Jiaran; Qiu, Rongxing; Lin, Jinqing
Abstract : Cooperative CO2 absorption by anion functionalized ILs with dual sites including amino acid group (AA) and basic anion (R) could be achieved through regulating the relative activation of two sites. Abstract : In this study, a variety of functionalized ILs with dual sites including amino acid group (AA) and basic anion (R) were synthesized to investigate the suppression and cooperation between the sites in CO2 absorption. The basic anions selected in this study with different basicity include sulfonate (Su), carboxylate (Ac), imidazolium (Im), and indolium (Ind). These ILs ([P66614 ]2 [AA–R]) were applied to CO2 absorption. The results present that CO2 capacity increases first and then decreases later with the continuous increase in the activity of the anion site. Combined with CO2 absorption experiments, IR and NMR spectroscopic analyses and DFT calculation demonstrate that the ability of one site to capture CO2 would be suppressed when the activity of another site is much stronger. Thus, the cooperation of dual site-functionalized ILs and high CO2 capacity might be achieved through balancing the two sites to be equivalent. Based on this point, [P66614 ]2 [5Am–iPA] was further synthesized by taking the advantage of the conjugated benzene ring. As expected, [P66614 ]2 [5Am–iPA] showed capacity as high as 2.38 mol CO2 per mol IL at 30 °C and 1 bar without capacity decrease even after 10 times recycling performance of CO2 absorption and desorption.